Meeting learners' needs inside the educational cloud. (1st January 2013) - Boyatt, Russell; Sinclair, Jane
Cloud computing provides a framework which can support many new possibilities for teaching and learning. Cloud-based services and applications are increasingly used by educational establishments to support many aspects of general and educational activity. There is also a related, growing emphasis on independent learning and open resources. The first part of this paper surveys current published work relating to education and the cloud. One noticeable aspect is that while there is a good deal written about infrastructure, technology and applications there is currently very little on pedagogy relating to the cloud. The second part of this paper considers one aspect of this relating to conceptual understanding and matching available resources to each individual's learning needs. We outline our work on a concept-based approach to user-assessment and to classification of learning materials, and consider how this can be used to personalise resource recommendation according to a concept model. We describe a prototype Moodle plug in developed to support this work.